Separation of acetylene from carbon dioxide and ethylene by a water-stable microporous metal – organic framework with aligned imidazolium groups inside the channels - Lee, Jaechul (2020)
Separation of acetylene from carbon dioxide and ethylene is challenging in view of their similar sizes and physical properties. Metal–organic frameworks (MOFs) in general are strong candidates for these separations owing to the presence of functional pore surfaces that can selectively capture a specific target molecule. Here, we report a novel 3D microporous cationic framework named JCM‐1. This structure possesses imidazolium functional groups on the pore surfaces and pyrazolate as a metal binding group, which is well known to form strong metal‐to‐ligand bonds. The selective sorption of acetylene over carbon dioxide and ethylene in JCM‐1 was successfully demonstrated by equilibrium gas adsorption analysis as well as dynamic breakthrough measurement. Furthermore, its excellent hydrolytic stability makes the separation processes highly recyclable without a substantial loss in acetylene uptake capacity.